THE EFFECT OF HEALTH EDUCATION WITH MEDIA IN FORM OF LEAFLET AND AUDIO VISUAL (VIDEO) ON HUSBAND KNOWLEDGE ABOUT THE DANGER SIGNS IN PREGNANCY AND POSTPARTUM IN 2017 - Diyah Sri Yuhandini; Dyah Widiyastuti (Journal of Maternity Care and Reproductive Health, 2021)
Husband’s support is highly needed in determining maternal health status. The ignorance of husband and family in recognizing complications, delays in knowing danger signs at home, and delays in health care facilities are quite fatal, namely death. Objective: To determine whether health education with leaflet and audio visual (video) has impacts on the husband’s knowledge of danger signs in pregnancy and childbirth.Methods: Quasi-experimental research used a two group pretest-posttest. The subjects were 30 husbands of pregnant women divided into 2 group, leaflet and videos. The data were analyzed using univariable and bivariable analysis with used Paired T-Test dan Uji Independent T- Test.Result: The mean knowledge before and after the intervention the video group with a p-value of 0.000 and leaflets group with a p-value of 0.026. Meanwhile, difference in the mean knowledge in the two groups with a p-value of 0.132. Conclusion & Recommendations: The mean knowledge of both groups experienced a significant increase before and after the intervention, but there was no significant relationship. The role of health workers is further enhanced in providing health education to husband about  danger signs in pregnancy and postpartum using audiovisual/video media and leaflets.